Особливості оповідної структури роману М. Кундери «Вальс на прощання»: музичний аспект - Шураєва, Надія; Shurayevа, Nadiya (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті розглянуто своєрідність оповідної структури роману М. Кундери «Вальс на прощання»; досліджено бінарні опозиції, музичний інтертекст та роль ігрового начала в поетиці М. Кундери; здійснено аналіз проблемно-тематичного й сюжетно-композиційного рівнів твору; зважаючи на яскравість і своєрідність музичного складника художнього світу письменника, висвітлено типологічні особливості заголовка роману; розкрито роль музики в художньому світі М. Кундери. In the article the peculiarity of the narrative structure of the novel by M. Kundera «The Farewell Waltz» was considered; the main features of the musical thinking of the writer were analyzed; the tonality, the rate, the rhythm and the range of the narration were characterized; the binary opposition, the musical intertext (images, associations, allusions) and the role of the playing origin in the poetic manner of M. Kundera were studied; the typological peculiarities of the heading of the novel were ascertained; the analysis of the problem-thematic and the plot-composition levels of the work was carried out; taking into account the vividness and the peculiarity of the musical component of the writer’s imaginative world, the interconnection of the musical and verbal text was traced; the specific character of the transformation of music into the author’s narrative (in particular, the artistic realization of the peculiarities of the musical genre of the sonata in the structure of the novel) was revealed and also the functional role of music in the novel «The Farewell Waltz» by M. Kundera was determined.
The Peculiarities of the Narrative Structure of the Novel by M. Kundera «The Farewell Waltz»: the Musical Aspect
Keywords: роман; оповідна структура; заголовок; музичний інтертекст; музична деталь; поліфонічність; проблематика; постмодерністський дискурс; novel; narrative structure; heading; musical intertext; musical detail; polyphony; problematics; postmodernist discourse